Utilisation of Quizlet App as a Student Performance Assessment tool by Teachers - Bambang Kustiawan (International Journal of Language and Ubiquitous Learning, 2024)
Background. Quizlet application for interactive learning used through online which can be used as an online learning media, which can be learned by teachers and students to increase vocabulary or also can make personal letters and official letters. It is useful to improve students' knowledge and skills in utilising Quizlet application as one of the applications in enhancing online learning. Purpose. The purpose of this study was to determine the utilisation of the Quizlet application as a student performance research tool by teachers. Method. This research uses quantitative methods, where data is obtained through interviews and distributing questionnaires. Results. The results of this study explain that the utilisation of the Quizlet application is very positive in the teacher's assessment of a student's performance. By using the Quizlet application, it is very helpful for students in learning that is difficult to understand, so that it can improve the learning process optimally. Conclusion. The conclusion of this study explains that Quizlet App can be used as a tool for assessing student performance by teachers in online implementation and can be used for language learning.